Larval optic nerve and adult extra-retinal photoreceptors sequentially associate with clock neurons during Drosophila brain development. - Malpel, S.; Klarsfeld, A.; Rouyer, F. (Development, 2002)
The visual system is one of the input pathways for light into the circadian clock of the Drosophila brain. In particular, extra-retinal visual structures have been proposed to play a role in both larval and adult circadian photoreception. We have analyzed the interactions between extra-retinal structures of the visual system and the clock neurons during brain development. We first show that the larval optic nerve, or Bolwig nerve, already contacts clock cells (the lateral neurons) in the embryonic brain. Analysis of visual system-defective genotypes showed that the absence of the afferent Bolwig nerve resulted in a severe reduction of the lateral neurons dendritic arborization, and that the inhibition of nerve activity induced alterations of the dendritic morphology. During wild-type development, the loss of a functional Bolwig nerve in the early pupa was also accompanied by remodeling of the arborization of the lateral neurons. Approximately 1.5 days later, visual fibers that came from the Hofbauer-Buchner eyelet, a putative photoreceptive organ for the adult circadian clock, were seen contacting the lateral neurons. Both types of extra-retinal photoreceptors expressed rhodopsins RH5 and RH6, as well as the norpA-encoded phospholipase C. These data strongly suggest a role for RH5 and RH6, as well as NORPA, signaling in both larval and adult extra-retinal circadian photoreception. The Hofbauer-Buchner eyelet therefore does not appear to account for the previously described norpA-independent light input to the adult clock. This supports the existence of yet uncharacterized photoreceptive structures in Drosophila.